Pengembangan Kemampuan Numerasi dalam Operasi Hitung Pecahan Melalui Penerapan Metode Experiential - Siti Arifah (Journal on Education, 2022)
The research aims to find out how the activities of teachers and students apply the Experiential Learning Method to Fractional Counting Operations material. In addition, it also aims to find out how to apply the Experiential Learning Method to develop Numeracy Skills in Fractional Counting Operations in grade 5 SD Negeri Wonokusumo VI/45 Surabaya. Numeration is the knowledge and skills to (a) use various numbers and symbols related to basic mathematics to solve practical problems in various contexts of everyday life and (b) analyze information presented in various forms (graphs, tables, charts, etc.) then use the interpretation of the analysis results to make predictions and make decisions. Cultural values ​​in Numeracy Ability can be effectively implemented if students have dynamic activities in actualizing these values. This ability is the basic capital to strive for the development of knowledge and the preservation of an educational culture which in this decade seems to have disappeared. Therefore, the application of the Contextual Learning Method, which in this study is the Experiential Learning Method, is important. The research was conducted with the mechanism of action of two cycles. And based on the results of the analysis of the results, it can be concluded that the Experiential Learning Method which is applied to develop Numeracy Ability in Fractional Counting Operations in grade 5 students at SD Negeri Wonokusumo VI/45 Surabaya is very effective and is highly recommended by the author to continue to be developed and applied according to the situation, the conditions and atmosphere of student learning so that the teaching and learning process continues to get appreciation and self-interest for students.